Zur Anatomie der Staatsquote - Klaus W. Zimmermann; Barbara Dluhosch (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2007)
Previous studies were plagued with considerable problems when interpreting and empirically analysing Wagner's Law. Therefore, we initially present some kind of "pure theory of government's share" for a two-person society based on the pure theory of public and private goods as originally developed by Samuelson. We show that Wagner's regime of a representative and authoritative individual and collective decision making – la Samuelson imply different government shares in GNP, though, in principle, Wagner's outcome can be generated even in a Samuelsonian context. Generalizing our results to an n-person society, we derive "optimal" government shares by use of various variants of the model, however, with very different distributional consequences.
urn:nbn:de:gbv:705-opus-17134
Keywords: H50; H11; H41; D11; 330; Wagner s Law; public goods; budget-to GNP-ratio